Atypical Manifestation of Disseminated Sporotrichosis in an AIDS Patient - Thiago Amparo Ferreira; Beatriz Moritz Trope; Glória Barreiros; Danielle Carvalho Quintela; Marcia Ramos- (Karger Publishers, 2018)
Sporotrichosis is an infection caused by fungi of the Sporothrix complex. The clinical lymphocutaneous presentation corresponds to the great majority of cases. With the increased incidence of sporotrichosis in the State of Rio de Janeiro, Brazil, atypical clinical forms have been reported with increasing frequency, usually associated with immunosuppression. We report the case of a 47-year-old female, with HIV and disseminated sporotrichosis, presenting molluscum-like skin lesions, as well as lung, nasal, and oral mucosa involvement. We also report the first demonstration of culture of Sporothrix in scales of the skin lesion, a fact not identified in the consulted literature.